2018
DOI: 10.1159/000490914
|View full text |Cite
|
Sign up to set email alerts
|

Is Thicker Choroid a Risk Factor for Malignant Glaucoma?

Abstract: Purpose: The aim of this study was to evaluate the choroidal thickness (CT) and its determinants in primary angle closure glaucoma (PACG) eyes with and without malignant glaucoma (MG). Methods: In this cross-sectional study, we enrolled 25 patients with bilateral primary angle closure (PAC) diseases; 1 eye of each patient was diagnosed with PACG initially and later with MG after trabeculectomy, and the fellow eyes were diagnosed with PACG, PAC, or PAC suspect. Thirty-seven eyes from 37 PACG patients were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
3
3
0
Order By: Relevance
“…Additionally, in this study, a thicker SFCT was found to be an associated factor for eyes with MG after adjusting for age, sex, AL, and IOP. The result of a thicker SFCT was compatible with the findings of our previous study that the choroidal thickness in eyes with MG increased during the onset of MG compared with control eyes with uncomplicated PACG ( 7 ). Similarly, Quigley et al and Zhang et al provided an assumption that choroidal expansion could play a significant role in the pathogenesis of PACG and even MG, which probably increases pressure in each compartment of the eye, causing a shallow anterior chamber ( 3 , 4 , 36 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, in this study, a thicker SFCT was found to be an associated factor for eyes with MG after adjusting for age, sex, AL, and IOP. The result of a thicker SFCT was compatible with the findings of our previous study that the choroidal thickness in eyes with MG increased during the onset of MG compared with control eyes with uncomplicated PACG ( 7 ). Similarly, Quigley et al and Zhang et al provided an assumption that choroidal expansion could play a significant role in the pathogenesis of PACG and even MG, which probably increases pressure in each compartment of the eye, causing a shallow anterior chamber ( 3 , 4 , 36 ).…”
Section: Discussionsupporting
confidence: 91%
“…However, there were no significant differences in the CVI, TCA, LA, SA and the SFCT between eyes with MG and the fellow eyes with non-MG. The results indicated that the fellow eyes with non-MG may have a similar anatomic structure of the choroid as eyes with MG, representing a potentially high risk of MG disease ( 7 , 17 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…These anatomical features of shorter AL, larger LV, and thinner and more anteriorly rotated ciliary body in younger PACD patients which are distinguished from the changing trend in normal people, might together lead to earlier onset of the disease. In addition, according to previous studies ( 7 , 8 , 21 , 34 ), these anatomical characteristics in young patients were also risk factors for the occurrence of malignant glaucoma after filtering surgery.…”
Section: Discussionsupporting
confidence: 58%
“…Ritch et al (5) defined "young" as "40 years old or younger" for the first time. Previous studies have found that younger PACD patients had a higher risk of malignant glaucoma after trabeculectomy (7,8), suggesting that the ocular biometric structure of younger patients might be different from that of older patients. However, most of the current studies on the ocular biometric parameters of PACD have focused on elderly patients (9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 97%